The gifted. The complete first season [videorecording (DVD)] - Nix, Matt (Twentieth Century Fox Home Entertainment, 2018)
The emotional story of a suburban couple whose ordinary lives are rocked by the sudden discovery that their children possess mutant powers. Forced to go on the run from a hostile government, the family seeks help from an underground network of mutants and must fight to survive. Connected to the X-Men film series, set in an alternate timeline where the X-Men have disappeared.